Competition-adjusted measures of real exchange rates - Ernesto Hugo Stein; Andrés Fernández Martin; Samuel Rosenow; Victor Zuluaga (Inter-American Development Bank (IDB), 2018)
We develop a methodology to construct real effective exchange rates that incorporate two distinctive elements not accounted for in the traditional measures: i) competition in third markets and ii) adjustments for similarity in export baskets between exporters and their competitors. In addition to constructing competition-adjusted real effective exchange rates at the aggregate country level, we develop similar measures at the country-product, country-destination, and country-product-destination level. We then build a novel and public dataset where we apply this methodology to compute monthly adjusted REERs for a panel of 120 countries and 769 products. As an application, we use the dataset to examine the changes in export competitiveness in countries in Latin America and the Caribbean between May 2014 and February 2016, a period characterized by substantial movements in exchange rates. We find that using traditional measures of real effective exchange rates misallocates between one third and one half of the relevant weights, and it leads to an important underestimation of the loss in export competitiveness. Furthermore, we find that there are very significant differences across products and destinations with regards to changes in export competitiveness.
Keywords: F10; F31; 330; Real effective exchange rate; Competitiveness; Trade